Good practice for transfer pricing in selected OECD countries - Szymczak, Magdalena (Dobre praktyki w zakresie cen transferowych w wybranych państwach członkowskich OECD, 2020)
Over the past decades the use of transfer pricing has increased significantly. It was noted that transfer pricing impacts on many areas of enterprise management. Countries, observing the gravity of the issue and taking care of securing their tax base, began to adopt regulations governing this matter. To meet the needs of both enterprises and regulators, international organisations have been working on developing guidelines and promoting them to adopt regulations on transfer pricing that are as clear and transparent as possible. Good practices included in the OECD Guidelines have become the most universally applicable. The paper aims to assess internationally developed solutions regarding transfer pricing based on the example of good practices contained in the OECD Guidelines regarding advance pricing agreements and mutual agreement procedures. The analysis covered all OECD Member States.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 119-130
Keywords: transfer pricing; OECD Guidelines; Advance Pricing Arrangements; MutualAgreement Procedure